Employee’s intention to stay, fit organization and organizational commitment: A conceptual framework - Ayesha, Noor; Yuserrie, Zainuddin; Panig, Shrikant Krupasindhu (International Symposium & Exhibition on Business and Accounting 2017 (ISEBA 2017), 2017)
The purpose of this paper is to develop a conceptual framework and research hypotheses based a thorough review of the conceptual and empirical research in the organizational behavior literature. Hypotheses indicate the relationships between organizational commitments, its antecedent, fit organization, including personal values and career goals and the outcome variable, employee’s intention to stay. Organizational commitment is hypothesized to have a mediating effect on the relationship between the fit organization and intention to stay. Implications for testing these hypotheses are articulated from research and practice perspectives. Conceptual framework from this paper will be used at the preliminary stage of the research on ICT industry that can be expected to contribute to the development of ICT workers in Malaysia